Efficacy and safety of anti-angiogenic drugs combined with chemotherapy in the treatment of platinum-sensitive/resistant ovarian cancer: a meta-analysis with trial sequential analysis of randomized controlled trials - He, Haining; Zhou, Fei (Frontiers in Pharmacology, 2024)
Background: With the emergence of new anti-angiogenic treatments and the ongoing updates to clinical guidelines, the effectiveness and safety of these agents in treating platinum-sensitive/resistant ovarian cancer (OC) are yet to be fully determined. Therefore, we conducted a meta-analysis to evaluate the efficacy and safety of anti-angiogenic drugs combined with chemotherapy (CT) for platinum-sensitive OC (PSOC ) or platinum-resistant OC (PROC). Methods: A comprehensive literature search was conducted across several databases, including PubMed, Web of Science, Embase, and the Cochrane Library, encompassing all pertinent randomized controlled trials (RCTs) up to May 31, 2024. The primary outcomes for the meta-analysis were progression-free survival (PFS) and overall survival (OS), while the objective response rate (ORR), adverse events (AEs) of any grade, and grade ≥ 3 AEs were considered secondary endpoints. Data synthesis involved the computation of hazard ratio (HR), relative risk (RR), along with their 95% confidence interval (CI) and prediction interval (PI). Trial sequential analysis was carried out using STATA 12.0, R software 4.3.1, and TSA v0.9.5.10 Beta software. Results: This meta-analysis encompassed 15 RCTs. The overall analysis revealed that compared to CT alone (or plus placebo), anti-angiogenic drugs combined with CT significantly improved PFS (HR [95% CI] = 0.573 [0.518-0.633], 95% PI: 0.383-0.876) and ORR (RR [95% CI] = 1.362 [1.260-1.472], 95% PI: 0.824-2.251), but also increased the incidence of grade ≥ 3 AEs (RR [95% CI] = 1.115 [1.070-1.162], 95% PI: 0.870-1.422) in PSOC patients. For PROC patients, this combination therapy notably improved PFS (HR [95% CI] = 0.542 [0.475-0.619], 95% PI: 0.322-0.930), OS (HR [95% CI] = 0.752 [0.646-0.875], 95% PI: 0.554-0.997), and ORR (RR [95% CI] = 2.141 [1.702-2.694], 95% PI: 0.839-5.307), whilst simultaneously elevating the risk of grade ≥ 3 AEs (RR [95% CI] = 1.487 [1.216-1.819]). Conclusion: Our research verified the advantages of combining anti-angiogenic agents with CT in enhancing PFS and ORR for patients with PSOC, and also confirmed improvements in PFS, OS, and ORR for those with PROC. It is crucial for medical practitioners to remain alert to the potential occurrence of AEs when implementing this combined therapeutic approach in a clinical milieu.